Profitabilitas pada perbankan syariah di Indonesia: Studi pengaruh faktor internal dan eksternal - Fadila, Indri Yaumil; Hermawan, Dadang (Journal of Islamic Economics and Business, 2021)
The purpose of this study is to find out and analyze internalÂ factors and external factors of Islamic banking that can affectÂ the profitability of Islamic Banking both simultaneously andÂ partially. The dependent variable used in this study is income smoothing which is proxied by Profitability which is proxiedÂ by the Return On Assets (ROA), while the independentÂ variables in this study are Capital Adequacy proxied by theÂ Capital Adequacy Ratio (CAR), Finance Risk proxied by NonÂ Performing Finance (NPF), Inflation, and BI Rate. ThisÂ research was conducted at Sharia Commercial Banks inÂ Indonesia for the period 2015. The population in this study isÂ Islamic banking in Indonesia and the sample used is ShariaÂ Commercial Banks in Indonesia, which until 2019 amounted toÂ 14 banks. The type of data used is secondary data that is dataÂ from the been published by Otoritas Jasa Keuangan. The typeÂ of data used is secondary data obtained from twww.ojk.comÂ and www.bi.go.id. The analysis technique used in this study isÂ Multiple Regression analysis using the SPSS 22 program tool. Kata kunci:Â Capital AdequacyÂ Ratio,Â Non PerfomingÂ Finance,Â Return On Asset,Â InflationÂ BI rate